2013
DOI: 10.1038/nphoton.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Functional patterned multiphoton excitation deep inside scattering tissue

Abstract: Light is the tool of the 21 st century. New photosensitive tools offer the possibility to monitor and control neuronal activity from the sub-cellular to the integrative level. This ongoing revolution has motivated the development of new optical methods for light stimulation. Among them, it has been recently demonstrated that a promising approach is based on the use of wavefront shaping to generate optically confined extended excitation patterns. This was achieved by combining the technique of temporal focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
123
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 52 publications
(69 reference statements)
9
123
1
Order By: Relevance
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 89%
“…Integrated with patterned illumination, the system could further be applied for functional excitation [17,28,29,31], 3D fabrication [30], and structured illumination purposes [39][40][41][42]. In this paper, we have demonstrated that the AEC would vary with different patterns at the same single spatial frequency and different orientations, and could reach nearly 29 % difference, e. g., from À11 % to + 18 % with 1.09 mm À1 spatial frequency patterns at the 908 and 08 orientations.…”
Section: Discussionmentioning
confidence: 89%
“…Heating is particularly relevant to experiments employing multiple focal points (e.g., Amir et al 2007;Bahlmann et al 2007;Bewersdorf et al 1998;Cheng et al 2011;Packer et al 2015;Papagiakoumou et al 2013;Voigt et al 2015), in which high total power is a greater concern than peak power at any one focus. The amount of heating tolerable in a given experiment depends on many factors, such as the duration and duty cycle of the experiment and the physiological variables being measured.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing optical effectors and reporters at high resolution within intact tissue usually relies on multiphoton absorption (e.g., Bahlmann et al 2007;Horton et al 2013;Packer et al 2015;Papagiakoumou et al 2013;Voigt et al 2015). The throughput of these methods increases with higher laser power, by addressing more foci in parallel or increasing signal rates from each.…”
mentioning
confidence: 99%
“…This ensures that excitation occurs primarily in a plane at the grating image location, with a thickness of around 10 μm or less for a microscope objective with a high numerical aperture. 3 The achievable axial resolution has been shown to be very similar to that of two-photon line-scanning microscopy. 4 It is expected that temporal focusing can excite samples as deep as, if not deeper than conventional two-photon microscopy, 5 but because conventional two-photon laser scanning microscopy can make use of the scattered emission photons in the sample (since all the emitted photons are assumed to come from the focal volume), unlike temporal focusing which can only use the ballistic and weakly scattered photons to form the image, it is expected that in scattering samples such as biological tissue samples, performance will be worse.…”
Section: Introductionmentioning
confidence: 80%
“…Some authors have attempted to define a metric based on various image parameters, 10 but the parameters are arbitrary and the threshold is set by defining a similarly arbitrary threshold that corresponds to an "acceptable" image. In one of the only papers to investigate the achievable tissue penetration depth of temporal focusing to date, Papagiakoumou et al 3 used the cross-correlation of a desired image versus a recorded one, but since the emitted photons were recorded in transmission geometry they were not scattered; hence, this experiment cannot be directly described as an investigation of the achievable imaging depth, but only one of the achievable excitation depth.…”
Section: Introductionmentioning
confidence: 99%